A Violaxanthin Deepoxidase Interacts with a Viral Suppressor of RNA Silencing to Inhibit Virus Amplification . Issue 4 (11th October 2017) - Chen, Ling; Yan, Zhaoling; Xia, Zihao; Cheng, Yuqin; Jiao, Zhiyuan; Sun, Biao; Zhou, Tao; Fan, Zaifeng
Abstract : Maize violaxanthin deepoxidase interacts with the HC-Pro protein of Sugarcane mosaic virus to attenuate its RNA-silencing suppression activity, contributing to decreased viral accumulation. Abstract: RNA silencing plays a critical role against viral infection. To counteract this antiviral silencing, viruses have evolved various RNA silencing suppressors. Meanwhile, plants have evolved counter-counter defense strategies against RNA silencing suppression (RSS). In this study, the violaxanthin deepoxidase protein of maize ( Zea mays ), ZmVDE, was shown to interact specifically with the helper component-proteinase (HC-Pro; a viral RNA silencing suppressor) of Sugarcane mosaic virus (SCMV) via its mature protein region by yeast two-hybrid assay, which was confirmed by coimmunoprecipitation in Nicotiana benthamiana cells. It was demonstrated that amino acids 101 to 460 in HC-Pro and the amino acid glutamine-292 in ZmVDE mature protein were essential for this interaction. The mRNA levels of ZmVDE were down-regulated 75% to 65% at an early stage of SCMV infection. Interestingly, ZmVDE, which normally localized in the chloroplasts and cytoplasm, could relocalize to HC-Pro-containing aggregate bodies in the presence of HC-Pro alone or SCMV infection. In addition, ZmVDE could attenuate the RSS activity of HC-Pro in a specific protein interaction-dependent manner. Subsequently, transient silencing of the ZmVDE gene facilitated SCMV RNA and coat protein accumulation. Taken together, our results suggest that ZmVDE interacts with SCMV HC-Pro and attenuates its RSS activity, contributing to decreased SCMV accumulation. This study demonstrates that a host factor can be involved in secondary defense responses against viral infection in monocot plants.